2014
DOI: 10.3732/ajb.1400356
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in gender strategies in Lycium (Solanaceae): Associations with ploidy and changes in floral form following the evolution of gender dimorphism

Abstract: Dimorphic sexual systems have likely evolved convergently in L. carolinianum. In contrast to previous studies, dimorphism is not perfectly associated with polyploidy. Although our sample from the Yucatán was both tetraploid and dimorphic, all populations in Hawaii were diploid regardless of sexual system. Ongoing phylogeographic and mating system studies will contribute to our understanding of reproductive evolution in this widespread, polymorphic species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 73 publications
2
37
0
Order By: Relevance
“…Given the high frequency with which dioecy evolves relative to self-incompatibility, this latter possibility is quite likely and has been well appreciated, for example, in the analysis and interpretation of the high frequency of dioecy in Hawaii (Sakai et al, 1995). Such evolutionary transitions to dioecy in self-compatible (SC) colonists are perhaps analogous to the evolution of dioecy following the loss of self-incompatibility in previously hermaphrodite lineages upon polyploidization (Miller & Venable, 2000;Pannell et al, 2004;Yeung et al, 2005;Blank et al, 2014). Indeed, both the origin of a new island lineage following long-distance dispersal and the origin of a new ploidy level can be viewed as 'accidental' events that break a connection with a parental population and facilitate adaptive evolution within a new (genetic or ecological) context.…”
Section: Reviewmentioning
confidence: 99%
“…Given the high frequency with which dioecy evolves relative to self-incompatibility, this latter possibility is quite likely and has been well appreciated, for example, in the analysis and interpretation of the high frequency of dioecy in Hawaii (Sakai et al, 1995). Such evolutionary transitions to dioecy in self-compatible (SC) colonists are perhaps analogous to the evolution of dioecy following the loss of self-incompatibility in previously hermaphrodite lineages upon polyploidization (Miller & Venable, 2000;Pannell et al, 2004;Yeung et al, 2005;Blank et al, 2014). Indeed, both the origin of a new island lineage following long-distance dispersal and the origin of a new ploidy level can be viewed as 'accidental' events that break a connection with a parental population and facilitate adaptive evolution within a new (genetic or ecological) context.…”
Section: Reviewmentioning
confidence: 99%
“…In fact, female flowers are almost always smaller than hermaphrodite flowers (reviewed in Delph, 1996 andShykoff et al, 2003;e.g. Bai et al, 2011;Barr and Fishman, 2011;Cuevas and López, 2011;Griffin and Byers, 2012;Blank et al, 2014;Cuevas et al, 2014) and/or they produce less nectar and pollen, leading to lower pollinator visitation rates (Delph, 1996;Ashman, 2000;Bai et al, 2011). On the other hand, the smaller size and number of flowers of female plants may also render them less attractive to enemies like florivores or seed herbivores, leading to a relatively higher seed output in females than hermaphrodites (Marshall and Ganders, 2001;Ashman, 2002;Asikainen and Mutikainen, 2005a;Collin and Shykoff, 2009;Clarke and Brody, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Miller & Venable () suggested that in Lycium polyploidy and gender dimorphism have evolved in concert (see also Ashman & al., ). However, recently, in L. carolinianum (Blank & al., ) dimorphism was not perfectly correlated with a higher ploidy level. As karyotypes of polyploids are difficult to make because homologous pairs are quite similar, there are no data to compare.…”
Section: Discussionmentioning
confidence: 83%